Registered letter - (:unkn) unknown (My University, 2011)
This is a Registered letter envelope with instructions on the front "This letter must be given to an officer of the post office to be registered and a receipt obtained for it." On the back of the envelope has a Trinidad 1 penny registration stamp. The envelope is dated 1915.
Colour: Sepia; Style: Landscape; Text: Blue
Keywords: Trinidad and Tobago; Postcards; Stamped envelopes--Trinidad and Tobago; Postal service--Registry system--Trinidad and Tobago; 1915; Stationery--Trinidad and Tobago; Envelopes (Stationery); Postal stationery--Trinidad and Tobago